2021
DOI: 10.3390/healthcare9101383
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Determinant of PTSD Symptoms among Home-Quarantined Chinese University Students during the COVID-19 Pandemic

Abstract: Background: When COVID-19 emerged in China in late 2019, most Chinese university students were home-quarantined to prevent the spread of the virus, considering the great impact of the lockdown on young people habits and their psychological well-being. This study explored the prevalence of post-traumatic stress disorder (PTSD) and its associated factors among Chinese university students who are isolated at home during the COVID-19 pandemic. Method: 4520 participants from five universities in China were surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The interventions proposed in the included studies can be divided into two broad categories: social support and coping strategies. Social support was provided by government authorities [ 49 , 52 - 54 , 61 , 62 , 68 , 72 , 84 , 86 - 88 ]; university authorities [ 12 , 48 , 50 , 51 , 53 - 55 , 57 - 59 , 62 , 64 , 65 , 67 , 69 , 91 , 93 ]; students’ affairs counselors and teachers [ 54 , 75 , 83 - 85 , 87 , 93 ]; family members [ 52 , 54 , 57 , 83 , 94 ]; health care authorities and professionals [ 52 , 63 , 66 , 75 , 77 - 79 , 87 ]; researchers [ 70 , 85 ]; and media-, internet-, and smartphone-based interventions [ 26 , 53 , 55 , 56 , 60 , 71 , 73 , 75 , 77 , 80 , 81 ]. Positive coping strategies were adopted by undergraduate students themselves [ 52 , 82 , 83 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interventions proposed in the included studies can be divided into two broad categories: social support and coping strategies. Social support was provided by government authorities [ 49 , 52 - 54 , 61 , 62 , 68 , 72 , 84 , 86 - 88 ]; university authorities [ 12 , 48 , 50 , 51 , 53 - 55 , 57 - 59 , 62 , 64 , 65 , 67 , 69 , 91 , 93 ]; students’ affairs counselors and teachers [ 54 , 75 , 83 - 85 , 87 , 93 ]; family members [ 52 , 54 , 57 , 83 , 94 ]; health care authorities and professionals [ 52 , 63 , 66 , 75 , 77 - 79 , 87 ]; researchers [ 70 , 85 ]; and media-, internet-, and smartphone-based interventions [ 26 , 53 , 55 , 56 , 60 , 71 , 73 , 75 , 77 , 80 , 81 ]. Positive coping strategies were adopted by undergraduate students themselves [ 52 , 82 , 83 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
“…Governments need to join hands with school administrators and various social parties to strengthen feasibility research to offer coping strategies, perform psychological interventions, and conduct relevant training [ 68 ]. Specifically, government authorities at all levels need to (1) specially improve efficacy appraisal through providing psychological backup for undergraduate students, by inviting psychiatrists to deliver relevant lectures [ 49 ]; (2) offer free psychological counseling via hotlines to help undergraduate students solve their psychological problems [ 53 ]; (3) develop interventions to improve undergraduate students’ various cognitive, behavioral, and psychosocial responses to public health emergencies such as COVID-19 [ 61 ]; (4) provide parents with relevant education and psychological counseling to help them understand their children’s mental state [ 62 ]; (5) advocate adequate social support and long-term targeted psychological intervention to provide more employment opportunities and develop mental health rehabilitation programs for the fourth-year undergraduate students who suffered more mental problems [ 72 , 84 ]; (6) pay special attention to mental health concerns induced by intolerance of uncertainty [ 86 ]; and (7) particularly care for students who have lost loved ones and experienced family financial losses [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the fear and uncertainty caused by COVID-19, such as dealing with online-based academic challenges, renegotiating parent–child relationships, and fear of bleak job prospects, has dramatically changed university students’ mental health and associated behaviors. 9–11 A high prevalence of mental, psychiatric, and behavioral health problems, such as PTSD, depressive symptoms, and sleep disturbances has been reported among this community. 4 , 12 Although the COVID-19 outbreak has been effectively controlled in mainland China, recent outbreaks in South and Southeast Asia, such as India 13 and Indonesia 14 and the rise in the delta variant have continued to challenge governments and medical institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers and policymakers have increasingly focused on the mental health status and adjustment caused by school closures and home confinement. In a previous study by this research team, we demonstrated the short-term psychological impact of the pandemic on the home-quarantined university students, revealing the presence of post-traumatic stress [ 17 ]. A longitudinal study by Wu S.Z.…”
Section: Introductionmentioning
confidence: 99%